Pengaruh Crank Shaf Deflection pada Auxiliary Engine/ Genset yang Melampaui Standart dan Strategi Mengembalikan ke Kondisi Ideal - Kurniawan, Ratna Dwi; Hariningrum, Rita (Marine Science and Technology Journal, 2024)
The dieselEgine that drives the ship's electric generator must always be maintained in good condition, because as a electrical power plant throughout the ship, without an electrict the ship cannot function normally. To keep it in top condition and prevent black out, diesel maintenance must be carried out according to standards so that this does not happen after damage has been repaired. One thing that must be done and reported to the classification is the crankshaft inspection. The aim of this research is to find out how much deflection occurs after several years of diesel engine operation, has it exceeded the specified standards? If it has exceeded how to return it to standard condition? The methodology used is quantitative and qualitative, by measuring directly on objects and comparing with existing standards, qualitative by direct observation in the field and comparing with existing references. From the existing results, conditions were obtained that exceeded standards, which were then repaired. The benefit of this research is that it provides an overview of how to carry out maintenance, measure, assess, and how to overcome problems that occur with the engine.